Relationship Between Knowledge Level of Adolescent Girls About The Effect of Warm Water on Dysminorhea Pain - Fransiska Marhaba; Tut Rayani Aksohini Wijayanti; Reny Retnaningsih (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Menstrual pain (dysmenorrhea) experienced by each woman is different, some are slightly disturbed but some are very disturbed to the point of being unable to carry out daily activities and making them have to rest or even be absent from school. Data in the UKS book records show that 16 female students were treated at the UKS where 13 (81.2%) complained of pain during menstruation. The purpose of this study was to determine the effect of warm compresses on reducing dysmenorrhea pain in female adolescents. The type of quantitative research with a pre-experimental research design on the one group pretest and post-test group design research approach. The population of this study was female adolescents who experienced menstrual pain with a sample of 30 female adolescents using a purposive sampling technique. Data collection used an observation sheet. Univariate and bivariate analysis (Wilcoxon test). The results of this study showed that the average menstrual pain in adolescents before being given warm compresses was 4.7 and after being given warm compresses was 1.4. There is an effect of warm compresses on reducing menstrual pain in female adolescents (p-value = 0.000). Advice for young women is to apply warm compresses to reduce pain during menstruation.